The Trojan Fish Strategy - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
How does an ornamental fish exporter grow its bottom line? Simple: By adopting and adapting the business model of the world’s most famous safety razor company. The Gillette Business Model, also known as Freebie Marketing, is much copied because of its simplicity: sell razors at a loss, or even give them away free, but make back your money with the disposable blade replacements. That same strategy has served many industries well